Consequências das orientações técnicas de matemática, realizadas pelos PCNP, na atuação dos professores e na aprendizagem dos alunos - Santos, Sara Margarida (2014)
The main objective of this research work, at the level of professional master's degree, is to analyse and evaluate whether the Technical Guidelines (TG), conducted by Professor of Mathematics Coordinator of Teaching (PMCT), from the Board of Education of Votorantim/SP have assisted or not in improving the performance of teachers in the classroom, their professional training as well as the consequences for the learning process of students. For this, I chose as the theme of work with teachers the "Introduction to Algebra". Studies carried out in Board of Education of Votorantim, between the years 2011 and 2013, indicated that issues related to this subject showed the lowest levels of learning in students of final years of elementary and high school. The choice of this theme, too, is justified by its importance in the possible contributions it brings to the students' learning about the transposition from the "mother tongue" to "mathematical/algebraic language" during the process of solving equations of the 1st degree. The research sought to answer the following questions: (1st) The Technical Guidelines of Mathematics, performed before the study, helped to improve the performance of teachers in the classroom, their professional backgrounds and the learning process of their students? (2nd) The amendments made during the search, the Technical Guidelines of Mathematics, on the topic "Introduction to Algebra", contributed to improving the performance of teachers in the classroom, towards their professional qualifications and learning their students? (3rd) With the modifications introduced in the Technical Guidelines of Mathematics, which the facilitating factors and difficulties to in-service training and the performance of teachers in the classroom were observed? (4th) What contributions to the planning, execution, analysis and discussion of research data brought to my training "trainer of trainers in mathematics" for Elementary School, the region of Votorantim/SP? and finally, (5th) What criticisms and recommendations can be made at the end of the research? The hypotheses that the guidelines agreed in TG, prior to the survey, were worked in the classroom and that it improved the development of specific mathematical skills of the students involved were not fully supported by research conducted. Consequently, research has brought me certain that the form of TG driving Mathematics, in DE-Votorantim, should be modified in the near future. Finally, this research has great contributions to my professional life, when it comes to math, didactic and pedagogical knowledge. In personal life I learned that I need to think/investigate the whys and how to encourage teachers under my supervision to realize that learning through discoveries are rewarding.